Social sciences and Complexity Devices - Martinez Diaz, Rodrigo; Zapata Domínguez, Álvaro (Cuadernos de Administración, 2013)
This paper presents a comparative perspective among traditional methods of qualitative and quantitative research and the potential of the new modeling and simulation paradigm for social science research, the different methods, and tools. We reviewed the criteria for the dynamic simulation of cellular automata and agents and outlined the concepts from artificial intelligence and artificial life, artificial societies and artificial culture, leading to a computational social science explanation. The study focuses on the Modeling and Agent-Based Simulation (ABMS, for the term in Spanish) as the quintessential device that allows understanding and explaning the emergence, evolution, and adaptation of social phenomena, rather than the typical prediction of other types of simulation. The ABMS methodology is positioned as a laboratory to modify the conditions of simulation of real phenomena, and allows constructing artificial societies where it is possible to perform experiments prevented by morals, ethics and/or costs in real life.